Intimate Violence : Anti-Jewish Pogroms on the Eve of the Holocaust - Kopstein, Jeffrey; Wittenberg, Jason, 1963- (Book collections on Project MUSE., 2018)
"This book employs archival research and statistical analysis on an original dataset of a summer 1941 wave of anti-Jewish pogroms to show that pogroms occurred not where antisemitism was strongest, but where local Jews challenged local non-Jews' dreams of national dominance"--